1996
DOI: 10.1007/s004010050459
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolethalus: a midline malformation syndrome with optic nerve coloboma and hypoplasia

Abstract: Ophthalmic pathological findings of hydrolethalus, a midline malformation syndrome, were determined in three fetuses aborted between the 14th and 19th gestational week. The eyes were serially sectioned and analyzed using light microscopy and a panel of 13 antibodies to neuronal, glial, epithelial, and mesenchymal elements of the eye. The general morphological and antigenic development of the anterior segment, retina and choroid were normal, but some lens fibers were vacuolated and irregular in all eyes. A colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Optic nerve hypoplasia (ONH) and optic nerve/fundus coloboma are common posterior ocular malformations in Swedish children with visual impairment (Blohmé & Tornqvist 1997a). Although ONH and coloboma are usually considered as separate clinical entities, they have been described as occurring in the same child (Hotchkiss & Green 1979; Slamovits et al 1989; Kivela et al 1996) (Filous et al 1998; Pecorella et al 2002) and it has been suggested that together they represent a spectrum of optic nerve abnormalities caused by an early insult to closely related embryonic structures (Brown 1982). ONH, thought to occur through an adverse prenatal advent affecting the anterior visual pathway (Frisen & Holmegaard 1978), may occur in isolation or with central nervous system (CNS) abnormalities and/or life‐threatening endocrinological insufficiencies (Brodsky & Glasier 1993; Brodsky et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Optic nerve hypoplasia (ONH) and optic nerve/fundus coloboma are common posterior ocular malformations in Swedish children with visual impairment (Blohmé & Tornqvist 1997a). Although ONH and coloboma are usually considered as separate clinical entities, they have been described as occurring in the same child (Hotchkiss & Green 1979; Slamovits et al 1989; Kivela et al 1996) (Filous et al 1998; Pecorella et al 2002) and it has been suggested that together they represent a spectrum of optic nerve abnormalities caused by an early insult to closely related embryonic structures (Brown 1982). ONH, thought to occur through an adverse prenatal advent affecting the anterior visual pathway (Frisen & Holmegaard 1978), may occur in isolation or with central nervous system (CNS) abnormalities and/or life‐threatening endocrinological insufficiencies (Brodsky & Glasier 1993; Brodsky et al 1997).…”
Section: Introductionmentioning
confidence: 99%